Perancangan Sistem Informasi Pengolahan Data Pelayanan Ibu Dan Anak Pada Posyandu Berbasis Web - Ardiansyah Farid; Khozainuz Zuhri; Hilda Dwi Yunita (Universitas Mitra Indonesia, 2022)
Currently information systems are developing very quickly and rapidly, including in the health sector. One of the uses of information systems in the health sector is the Integrated Service Post (Posyandu). In general, Posyandu is a form of Community-Based Health Efforts (UKBM) which is managed from, by, for and with the community. Based on this, the researchers proposed a Mother and Child Data Processing system at Posyandu. The presence of Posyandu can indirectly provide convenience to the community, but raises new problems, namely the large amount of data on mothers and children participating in the Posyandu program, causing reports and archives of Posyandu activities to accumulate at the coordinator. In addition, problems in finding data are due to the large amount of data which causes a lack of control over children. Therefore, this research produces a web-based data processing system that can process data storage more securely, assist in data retrieval and minimize errors when inputting patient data at Posyandu. With the presence of this data processing system, it can help Posyandu cadres work more quickly and precisely in helping the community in terms of health, especially pregnant women and toddlers (children).